Art. 372, 373 und 378-380 ZPO - Müller, Christoph (Zurich/Bâle/Genève: Helbing Lichtenhahn, 2013)
Mueller, C. (2013). Art. 372, 373 und 378-380 ZPO, in: T. Sutter-Sohm/F. Hasenböhler/C. Leuenberger (éd.) Kommentar zur Schweizerischen Zivilprozessordnung (ZPO), 2e éd., pp. 2656-2680 et pp. 2706-2723, Zurich/Bâle/Genève: Helbing Lichtenhahn